Channel Distribution Performance in Cold Chain Management: A Comparative Scenario Between Two States of India - Saha, Shantanu; Mukherjee, K.; Chandra, B. (Indian Journal of Marketing, 2015)
This paper attempted to study the performance of channel distribution in cold storage operations and inter-alia issues in an attempt to give new insights into cold storage operations. An exploratory study was carried out by interviewing, interacting, and sharing of experiences by as many as 64 cold storage operators spanning from various districts of Punjab and Uttar Pradesh. The comparison of operations of cold storage in these two states brought forth that channel distribution plays an important role in maintaining and delivery of perishable products from cold storage to retail markets. The study is expected to assist in creating insights on issues relevant to the involvement of channel intermediaries in cold storage operations.